Beyond Linear Delay Multipliers in Air Transport - Seddik Belkoura; José Maria Peña; Massimiliano Zanin (Journal of Advanced Transportation)
Delays are considered one of the most important burdens of air transport, both for their social and environmental consequences and for the cost they cause for airlines and passengers. It is therefore not surprising that a large effort has been devoted to study how they propagate through the system. One of the most important indicators to assess such propagation is the delay multiplier, a ratio between outbound and inbound average delays; in spite of its widespread utilisation, its simplicity precludes capturing all details about the dynamics behind the diffusion process. Here we present a methodology that extracts a more complete relationship between the in- and outbound delays, distinguishing a linear and a nonlinear phase and thus yielding a richer description of the system’s response as a function of the delay magnitude. We validate the methodology through the study of a historical data set of flights crossing the European airspace and show how its most important airports have heterogeneous ways of reacting to extreme delays and that this reaction strongly depends on some of their global properties.